2012
DOI: 10.1002/ab.21446
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Teacher Preference for At‐Risk Children's Social Status

Abstract: Aggressive behaviors have been associated with social costs (e.g., rejection) and benefits (e.g., popularity) in previous studies. The current study sought to examine the moderating effect of teacher preference on the association between distinct forms of aggressive behavior (i.e., physical aggression and relational aggression) and social status (i.e., rejection and popularity), and to explore whether these associations differed for boys and girls. Fourth and fifth grade students (N = 193) completed peer nomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…This finding is consistent with the literature showing that high academic achievers were usually popular among peers and teachers and were often designated as teachers' pets (Babad, 2000;Chiu, Lee, & Liang, 2013;Moore et al, 2012;Tal & Babad, 1989. Because students who perform well academically give teachers much satisfaction, it was not surprising to find that teachers showed a preference towards them.…”
Section: Behavioral Profilessupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is consistent with the literature showing that high academic achievers were usually popular among peers and teachers and were often designated as teachers' pets (Babad, 2000;Chiu, Lee, & Liang, 2013;Moore et al, 2012;Tal & Babad, 1989. Because students who perform well academically give teachers much satisfaction, it was not surprising to find that teachers showed a preference towards them.…”
Section: Behavioral Profilessupporting
confidence: 80%
“…While teachers' preferences appear to play an important role in determining children's social status among peers (Birch & Ladd, 1997;Mercer & DeRosier, 2008;Moore, Shoulberg, & Murray-Close, 2012), this premise has not been empirically tested. Therefore, the purpose of the current study was to re-conceptualize and operationalize peer status using both teachers' and peers' preferences to generate a two dimensional model with four possible social status categories.…”
Section: Introductionmentioning
confidence: 99%
“…Participants' family income levels ranged from $6,000 to $750,000 ( M = $92,826; SD = $70,305). The education level of participants' parents ranged from 4 to 17 years of school completed ( M = 15.34; SD = 2.01; see Moore, Shoulberg, & Murray‐Close, for additional information about the sample).…”
Section: Methodsmentioning
confidence: 99%
“…We cannot rule out that the link between popularity and increases in teacher–pupil conflict is also mediated by aggression in special education. Interestingly, regular education studies show that not only aggression toward peers relates to maintaining a social position, but also that conflict with the teacher is related to gaining popular status among peers (De Laet et al, 2014; Moore et al, 2012). The conflictual interactions of pupils with the teacher may also be interpreted as ways to defy the teacher’s authority, which, in the eyes of classmates, may enhance the reputation of these pupils and increase their social position in the classroom hierarchy (De Laet et al, 2014; Moore et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have investigated associations between TCRs and popularity . A cross-sectional study by Moore, Shoulberg, and Murray-Close (2012) found that popularity was negatively related to teacher’s satisfaction with the relationship, especially for boys. A longitudinal study by De Laet and colleagues (2014) reported that higher levels of teacher–pupil conflict were associated with increased popularity across school years.…”
Section: Bidirectional Associations Between Tcrs and Social Statusmentioning
confidence: 99%